Comparison of Outcomes between Clopidogrel and Ticagrelor in Patients Undergoing Primary Percutaneous Coronary Intervention in Acute Myocardial Infarction - Pelluri, Ranakishor; Prasad, Thiruvaipati Sai; Madhuri, Chandu; Supriya, Kommanaboina; Mukharjee, Kamma Sri Pandu; Prasad, SYG; Susmitha, Rebba Sai; Radha, Chinta Indu; Prasanna, Pydala Sai; Srinivasababu, Puttagunta (Indian Journal of Pharmacy Practice)
Background: Ticagrelor is more potent than clopidogrel, but it is not known whether this translates into clinical benefit is not well explored in patients undergoing primary Percutaneous coronary intervention (PCI) with aspirin for ST elevation myocardial infarction patients. Aim: To assess the improvement of therapeutic outcomes between clopidogrel and Ticagrelor in patients undergoing primary Percutaneous coronary intervention (PCI) in AMI patients. Methodology: It was a prospective observational study conducted at Ramesh hospital, Guntur, during the period of August 2017 to March 2018 (8 months). The study was approved from Institutional Human ethics committee. A 60 patients were enrolled with ACS with elapsed time between 12-24hrs of symptom onset. Before reperfusion therapy, they are treated with Aspirin, Clopidogrel/Ticagrelor before PPCI and after PPCI. Our study was aimed to safety and efficacy of anti-platelet drugs (Clopidogrel and Ticagrelor) after PPCI. Results: The clinical outcomes of our study TIMI grade-3 flow was observed in 4 patients (13.33%) of clopidogrel group and 7 patients (23.33%) in Ticagrelor group. The mean TIMI flow was observed in clopidogrel are 1.60 and 2.00 in Ticagrelor pretreated patients. Ticagrelor group patients had better TIMI flow than clopidogrel. The pumping capacity of the heart LVEF more than 50% was observed in Clopidogrel pretreated patients 8 (26.66) with the mean score of 1.0 and> 50% was observed in Ticagrelor pretreated patients 16 (53.33%) with the mean score of 1.46. The mean score of ECG changes in clopidogrel were 0.50 and in Ticagrelor pretreated patients are 0.66. There four there is no significant difference was observed in ST Segment resolution in Clopidogrel and Ticagrelor pretreated patients. The Regional Wall motion (abnormalities (RWMA) are observed that in Clopidogrel pretreated patients 9 (30.00%) are with Hypokinetic with the mean score of 1.86 and in Ticagrelor pretreated patients 14 (46.66%) with the mean score of 2.10 respectively. Therefore Ticagrelor shows more efficacious than Clopidogrel in all aspects, except ECG (ST segment resolution) changes. Conclusion: The findings in our study concludes that the Ticagrelor was more efficacious than clopidogrel and we are not observed any adverse drug reaction with both Ticagrelor and clopidogrel.
Keywords: Clopidogrel; Ticagrelor; PPCI; Safety; Efficacy.